Preparatory and introductory exercises in fire training of police officers - Polyansky P.G.; Chernykh V.V. (Theory and Practice of Physical Culture, 2025)
Introduction. In educational institutions of the Russian Ministry of Internal Affairs system, as part of the implementation of the main programs of professional training of persons first accepted into the internal affairs bodies for the position of "Policeman", training sessions on firearms training are provided [1]. An analysis of the practice of teaching firearms training revealed the need to develop the use of preparatory and introductory physical exercises aimed at training police officers in the use of service weapons [2]. Purpose of the research – development of sets of preparatory and introductory physical exercises aimed at training police officers in the use of service weapons. Research methodology and organization. The study was conducted in 2024 at the Tyumen Institute for Advanced Training of Employees of the Ministry of Internal Affairs of Russia. The study used scientific methods: analysis and generalization of scientific and methodological literature and experience in teaching fire training, systematization and classification of preparatory and preliminary physical exercises. Results and its discussion. As a result of the study, a set of preparatory and introductory exercises was developed aimed at training police officers in the use of service weapons. Preparatory exercises in fire training of patrol police officers are considered by us as physical exercises aimed at preparing the employee’s motor apparatus to perform shooting exercises from service weapons. We consider preparatory physical exercises in fire training for patrol police officers as physical exercises similar in structure to individual movements included in the motor action of shooting from a service weapon. The developed sets of physical exercises were tested in fire training classes as part of the implementation of professional training programs for individuals for the position of "Police Officer". Conclusion. The results of the study revealed the effectiveness of a set of preparatory and introductory exercises aimed at training police officers in the use of service weapons. The students in the experimental group demonstrated a higher level of proficiency in service weapons at the final lesson (18.6% more than in the control group).